Hot fomentation of newborn fontanelles as an indigenous practice in Ghana: implications for policy and integrated community‑based health care in Covid‑19 pandemic and beyond - Ani‑Amponsah, M.; Richter, S.; Adam, M.A-H.; Osei, E.A.; Mustapha, M.; Oti‑Boadi, E. (International Journal for Equity in Health, 2023)
Objective African newborns undergo numerous traditional and religious practices ranging from fontanelle fomentation to total head shaving, scalp molding, skin scarification and ano-genital irrigation which can negatively impact the health of neonates. Hot fomentation of fontanelles has been a predominant indigenous home-based postnatal practice in Ghana and among Africans in the diaspora. Mobility restrictions during the Covid-19 pandemic has impacted direct access to facility-based care as well as home care. The fourishing of newborn traditional practices among African populations during this Covid-19 pandemic offers opportunities to rethink the provision of family healthcare sup‑ port for newborns during the ongoing pandemic and beyond. Hence, the aim of this critical review was to examine and describe a common indigenous practice—hot fontanelle fomentation to inform home birth support, discharge planning, and the delivery of optimal home-based care support. Study design This study is a review of literature on hot fomentation of newborn fontanelles. Methods Literature search in CINAHL, PubMed, African Index Medicus and Scopus, was conducted and evidence synthesised from articles ranging from 1983–2022. Sixty articles were reviewed; however, 10 manuscripts were excluded prior to screening. The other 19 were exempted because they were either below 1983 or were not the best ft for the study purpose. In all, 31 studies were included in the study. The study was guided by Madeleine Leininger’s Culture Care Diversity and Universality care theory. Results The current study identifies hot fomentation of newborn fontanelles practices in Ghana, the description of hot fomentation practices and the dangers associated with it. The findings and suggested ways to help overcome this challenge. Conclusion There are several neonatal indigenous practices including fontanelle fomentation which pose threat to the health of the neonate as discussed in this study. Future research needs to investigate innovative ways of fontanelle fomentation where necessary instead of the use of hot water by mothers, especially in this Covid-19 pandemic where health and mobility restrictions impact physical access to timely health care. This research will help educate mothers about the dangers of fontanel fomentation and reduce the practice, especially in rural areas of developing countries. This could help reduce neonatal mortality and unnecessary healthcare costs.
Research Article
Keywords: Newborn; Hot fontanelle fomentation; Indigenous practice; Ghana; Covid-19